Oxygen-regulated expression of the RNA-binding proteins RBM3 and CIRP by a HIF-1-independent mechanism - Wellmann, Sven; Bührer, Christoph; Moderegger, Eva; Zelmer, Andrea; Kirschner, Renate; Koehne, Petra; Fujita, Jun; Seeger, Karl (Journal of cell science, 2004)
The transcriptional regulation of several dozen genes in response to low oxygen tension is mediated by hypoxia-inducible factor 1 (HIF-1), a heterodimeric protein composed of two subunits, HIF-1alpha and HIF-1beta. In the HIF-1alpha-deficient human leukemic cell line, Z-33, exposed to mild (8% O(2)) or severe (1% O(2)) hypoxia, we found significant upregulation of two related heterogenous nuclear ribonucleoproteins, RNA-binding motif protein 3 (RBM3) and cold inducible RNA-binding protein (CIRP), which are highly conserved cold stress proteins with RNA-binding properties. Hypoxia also induced upregulation of RBM3 and CIRP in the murine HIF-1beta-deficient cell line, Hepa-1 c4. In various HIF-1 competent cells, RBM3 and CIRP were induced by moderate hypothermia (32 degrees C) but hypothermia was ineffective in increasing HIF-1alpha or vascular endothelial growth factor (VEGF), a known HIF-1 target. In contrast, iron chelators induced VEGF but not RBM3 or CIRP. The RBM3 and CIRP mRNA increase after hypoxia was inhibited by actinomycin-D, and in vitro nuclear run-on assays demonstrated specific increases in RBM3 and CIRP mRNA after hypoxia, which suggests that regulation takes place at the level of gene transcription. Hypoxia-induced RBM3 or CIRP transcription was inhibited by the respiratory chain inhibitors NaN(3) and cyanide in a dose-dependent fashion. However, cells depleted of mitochondria were still able to upregulate RBM3 and CIRP in response to hypoxia. Thus, RBM3 and CIRP are adaptatively expressed in response to hypoxia by a mechanism that involves neither HIF-1 nor mitochondria.